Sub-chronic toxicity study of synthetic Pyrethroids (Lambda-cyhalothrin) on reproductive organs of male Wistar rats (2016)
Pesticides constitute the most widespread environmental contaminants due to their ubiquitous use in all aspect of human endeavors. Lambda-cyhalothrin (LTC), a synthetic pyrethroid has widely been used for pest control. Human and animals are occasionally and unintentionally exposed to lethal and sub-lethal doses of pesticides stemming from its various uses to control pests both in agriculture and public health. The objective of the study was to evaluate the toxicity of LTC in male reproductivity through testicular tests. The study also investigated the haematological, serum biochemistry and histological effects of sub-chronic concentrations of LTC on male rats. Twenty-five 7-weeks-old male Wistar rats (Rattus norvegicus) were randomly assigned to five groups. Group 1 was the control group, which received distilled water. Experimental groups 2, 3, 4 and 5 received by gavage 25, 50, 75 and 100 mg/kg LTC body weight, respectively, of LTC over a period of five weeks. Histopathological studies were carried out on the testes and seminal vesicles at the end of the experiment. A significant decrease in the absolute weight of testes and seminal vesicles, sperm count, sperm motility and L-D ratio was observed. The results obtained also show marked degeneration of spermatogenic cells associated with interstitial necrosis and congestion with interstitial diffuse edema in the testis of the rat treated with LTC. A typical dose-dependent hyperplasia and degeneration of the seminal vesicles was found in all LTC treated rats with 100 mg/kg body weight and 25 mg/kg body weight having the highest and lowest toxicity level respectively, when compared with that of Group 1. It can be concluded that LTC is highly toxic and may induce poor fertility, cell damage and anaemic conditions in exposed rats.